2017
DOI: 10.1177/0891988716686834
|View full text |Cite
|
Sign up to set email alerts
|

The Moderating Role of Insulin-Like Growth Factor 1 in the Relationship Between Cognitive and Aerobic Endurance Change

Abstract: The relationship between cognitive and aerobic endurance change varies as a function of IGF-1 in persons with MCI. Additional work is needed to clarify the mechanisms of these findings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 32 publications
(39 reference statements)
0
6
0
Order By: Relevance
“…Liu et al (2020) reported that neither strength nor aerobic exercise had a significant effect on IGF-1 levels. In the study by Anderson et al (2017) researchers found that contrary to the study expectations, greater exercise endurance was associated with poorer cognitive prognosis when serum IGF-I levels were above a certain level (73.96 ng/mL). They concluded that the higher IGF-I levels might indicate disease progression within their sample, potentially as a compensatory response, and therefore participants with higher IGF-I levels may be less likely to benefit from the intervention.…”
Section: Hormonal Measuresmentioning
confidence: 69%
See 2 more Smart Citations
“…Liu et al (2020) reported that neither strength nor aerobic exercise had a significant effect on IGF-1 levels. In the study by Anderson et al (2017) researchers found that contrary to the study expectations, greater exercise endurance was associated with poorer cognitive prognosis when serum IGF-I levels were above a certain level (73.96 ng/mL). They concluded that the higher IGF-I levels might indicate disease progression within their sample, potentially as a compensatory response, and therefore participants with higher IGF-I levels may be less likely to benefit from the intervention.…”
Section: Hormonal Measuresmentioning
confidence: 69%
“…Insulin-like growth factor (IGF-I) is a peptide hormone that functions primarily to stimulate growth but that also possesses some ability to decrease blood glucose levels, having insulin-like actions in some tissues, though far less potent than insulin in decreasing blood glucose concentrations [Britannica Dictionary (science division), 2019]. IGF-I levels were measured in studies by Anderson et al (2017), Baker et al (2010), Liu et al (2020), and Tsai et al (2018Tsai et al ( , 2019. In these studies, results were mixed, with Tsai and colleagues reporting some acute exercise increases in IGF-I levels, but indicating that these increases might not be sustained following completion of the activity.…”
Section: Hormonal Measuresmentioning
confidence: 99%
See 1 more Smart Citation
“…The study sites are laboratories at the Department of Kinesiology and the Gateway MRI Center at the University of North Carolina at Greensboro located in Greensboro, North Carolina, USA, along with local YMCAs where the PA intervention is provided. This study was approved by the university's Office of Research Integrity and this protocol is reported in accordance with the [49]; Exercise responsive [50,51]; Binds to tropomyosin-related kinase B (TrkB) receptor, ↑ glucose uptake, interacts with autonomic nervous system [42] SAP Biomarker of progression to AD [52,53] Albumin Neuroprotective due in part to anti-oxidative properties [53,54] Glucose Levels altered by exercise and related to irisin and/or BDNF; high levels have negative effect on neuroplasticity [55,56] IGF-I Interacts with BDNF in response to exercise; neural plasticity [57][58][59] APOE Linked to Aβ clearance and lipid homeostasis [53,60] alpha-2 macroglobulin Proteinase inhibitor associated with AD disease severity [53,61] Insulin Altered by exercise and irisin; ↑ insulin sensitivity [62,63] Irisin Exercise ↑ FNDC5/irisin release from muscle; ↑ BDNF transcription in hippocampus [42,64,65] TNF-α Pro-inflammatory [66,67]; related to dementia [68,69] AD Alzheimer's disease, APOE apolipoprotein epsilon 4 allele, BDNF Brain-derived neurotrophic factor, CRP C-reactive protein, FNDC5 fibronectin type III domain containing 5, IGF insulin-like growth factor, IL interleukin, SAP serum amyloid P, TNF Tumor necrosis factor SPIRIT guidelines [100]. See the SPIRIT checklist in additional file 1 for more information.…”
Section: Study Design and Settingmentioning
confidence: 69%
“…Insulin like growth factor (IGF-1) is a neurohormone with both direct and indirect influences on neurocognitive functions, primarily induced through exercise training [270,271]. IGF-1 appears to have important regulatory effects on both BDNF and VEGF, and may therefore have a critical moderating influence on other growth factor influences within the CNS [251].…”
Section: Neurotrophins / Growth Factorsmentioning
confidence: 99%